1 | initial version |

As you can see `eq2`

is a list containing a single element:

```
sage: eq2
[b == -a + d]
```

To get it, just type

```
sage: eq2[0]
b == -a + d
```

Now this equality has two sides. You can get its left hand side, and right hand side as folows:

```
sage: eq2[0].left_hand_side()
b
sage: eq2[0].right_hand_side()
-a + d
```

or simply:

```
sage: eq2[0].lhs()
b
sage: eq2[0].rhs()
-a + d
```

2 | No.2 Revision |

As you can see `eq2`

is a list containing a single element:

```
sage: eq2
[b == -a + d]
```

To get it, just type

```
sage: eq2[0]
b == -a + d
```

Now this equality has two sides. You can get its left hand side, and right hand side as folows:

```
sage: eq2[0].left_hand_side()
b
sage: eq2[0].right_hand_side()
-a + d
```

or simply:

```
sage: eq2[0].lhs()
b
sage: eq2[0].rhs()
-a + d
```

So, i guess what you are looking for is:

```
sage: eq3=c/eq2[0].rhs()
sage: eq3
-c/(a - d)
```

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.